The Role of Islamic Finance in Global Climate Action: Systematic Literature Review and Text Mining - Aryadimas Suprayitno (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
This study explores the role of Islamic finance in global climate action through a systematic literature review and text mining analysis. Using the Scopus database, 23 English-language articles published between 2016 and 2026 were systematically selected and analyzed. The study aims to identify dominant research themes, Islamic financial instruments, and conceptual developments related to climate change mitigation and sustainable finance. Clustering analysis identifies three dominant themes: green Islamic finance and sustainable investment, Islamic banking and carbon emission reduction, and renewable energy financing and climate mitigation. Text mining results show that “sukuk” is the most dominant financial instrument discussed in the literature, highlighting the strategic role of green sukuk in financing renewable energy, sustainable infrastructure, and low-carbon development projects. The study also finds that Islamic banking has potential to support environmental sustainability, although its effectiveness depends on governance quality and sustainability integration. However, Islamic social finance, Islamic carbon credit systems, and green Islamic equity investments remain underdeveloped within current climate finance discussions.